Analisis Sudut ATD pada Narapidana - Nurul Aida; Dewi Imelda Roesma; Djong Hon Tjong (Universitas Andalas, 2015)
Research on dermatoglifi and ratio 2D: 4D has been done in April to June 2013 by Stratified Random method for inmates and Random Simple (Simple Random Sampling) for non-inmates. Data processing is carried out in the Laboratory of Cytology and Genetics, Department of Biology, Faculty of Mathematics and Natural Sciences Andalas University in Padang, West Sumatra.Keywords: dermatoglifi, fingerprint patterns, inmates